Convective drying of yellow discarded onion (Angaco INTA): Modelling of moisture loss kinetics and effect on phenolic compounds - Roman, María Celia (2019)
The Angaco INTA onion variety is the most cultivated and its production, mostly is destined for export. Due to their high-quality standards of these markets, many onions are discarded. The drying process seems to be a promising solution that not only give added value to this product, but also extend shelf life. In this work, the influence of convective drying process, at 60 and 70 °C, on the kinetic behavior, antioxidant activity, phenolic and flavonoid contents of discarded onion slices were investigated. Considering that, the Angaco INTA onion is a variety genetically developed to have shorter cultivation times in this region; the phenolic compounds content in this onion variety, the drying kinetics and its influence on this content have never been studied. In this study, the phenolic compounds contributions to dehydrated product quality was evaluated, observing that the convective drying increased the total soluble phenolic and flavonoid contents and antioxidant properties for both temperatures, being highest at 70 °C. The rehydration ratios were similar to the slices dried at 60 and 70 °C. Several models were used for describing the obtained drying curve equation of onion slices, being the Midilli’s model the one that presented the best fit. Ficks’s model of water diffusion fitted all experimental data with acceptable correlation coefficients. Considering the achieved findings, 70 °C is the optimum temperature to produce the dehydrated Angaco INTA onion.